2020
DOI: 10.1016/j.fuel.2020.117807
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the wetting state of minerals in complex sandstone rock in-situ by Atomic Force Microscopy (AFM)

Abstract: Low salinity waterflooding is a low-cost method of enhancing oil recovery although, no consistent concept has been established explaining why some oil-fields show an increase in oil production when the salinity of the injected brine is reduced, while others do not. Various studies were conducted investigating the underlying mechanisms of the 'low salinity effect' using different crude oil, brine and rock compositions. Core floods of sandstone rock and analyses of molecular interactions using model systems indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 73 publications
1
7
1
Order By: Relevance
“…The decrease in A fo in the altered case is consistent with qualitative observations by ref , which reported water film propagation and enlargement during LSWF, leading to the detachment of oil from the rock surface and, therefore, a decrease in A fo . These results also broadly agree with pore-scale observations of a change in wetting state during low-salinity flooding made using contact angle measurements , and subpore scale observations of wetting alteration during low-salinity flooding using atomic force microscopy. , …”
Section: Resultssupporting
confidence: 86%
“…The decrease in A fo in the altered case is consistent with qualitative observations by ref , which reported water film propagation and enlargement during LSWF, leading to the detachment of oil from the rock surface and, therefore, a decrease in A fo . These results also broadly agree with pore-scale observations of a change in wetting state during low-salinity flooding made using contact angle measurements , and subpore scale observations of wetting alteration during low-salinity flooding using atomic force microscopy. , …”
Section: Resultssupporting
confidence: 86%
“…These studies focused on flat areas within the rock as these were identified as original crystal facies unaffected by the sample preparation and because an effect of surface roughness on the investigated molecular interactions between the functionalized tip and the surface could be excluded [30]. In more recent studies, AFM was also used to assess the impact of the surface structure on the fluid configuration and molecular interactions by scanning the original internal rock surface, thus avoiding invasive sample preparations [31,32]. These studies have demonstrated the impact of surface features in the range of 100 nm-10 µm but missed the range below, which is required to link the larger-scale wetting response with the underlying molecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate prediction of multiphase flow in the soils and the subsurface for geoenvironmental issues including Carbon Capture and geological Storage, water resources remediation, or Enhanced Oil Recovery requires an in-depth understanding at the pore-scale of the key mechanisms that influence the fluid displacements and dynamics including viscous and capillary forces but also the solid surface wettability. Recent studies have shown that the spatial distribution of wettability play a crucial role (AlRatrout et al, 2018;Yesufu-Rufai et al, 2020). The rock wettability and the resulting multiphase flow can be modified by a change in pore water composition (pH, salinity) and interfacial physicochemical properties.…”
Section: Modeling Of Wettability and Interfacial Propertiesmentioning
confidence: 99%